Vegetable production and household poverty reduction in Ludewa district - Mlelwa, Faraja (Mzumbe University, 2023)
A dissertation submitted in partial fulfilment of the requirement for the Degree of Master of Science in Development Policy (MSc. DP) of Mzumbe University Mzumbe University